2019
DOI: 10.3390/ijerph17010191
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents’ Views on Seeking Help for Emotional and Behavioral Problems: A Focus Group Study

Abstract: This study aimed to get insight into adolescents’ views on help-seeking for emotional and behavioral problems. Fourteen focus groups were conducted. Two vignettes, depicting one healthy adolescent with few issues and one adolescent with severe psychosocial problems, were used to structure the focus groups. The focus groups were framed within a youth help-seeking model. Adolescents (mean age of 15.0 years) generally reported seeking help from friends or the internet for mild issues and from a person they trust … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 33 publications
2
8
0
Order By: Relevance
“…The present study partially confirmed the assumption that friendships improve the formation of peer support ties. The result that dyadic friendship relationships positively affected the formation of dyadic support relationships is consistent with previous theories of the relationship between friendship and support seeking ( Barbee and Cunningham, 1995 ; van den Toren et al, 2020 ). Furthermore, a kind of triadic friendship improved peer support relationships.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The present study partially confirmed the assumption that friendships improve the formation of peer support ties. The result that dyadic friendship relationships positively affected the formation of dyadic support relationships is consistent with previous theories of the relationship between friendship and support seeking ( Barbee and Cunningham, 1995 ; van den Toren et al, 2020 ). Furthermore, a kind of triadic friendship improved peer support relationships.…”
Section: Discussionsupporting
confidence: 90%
“…Friendships can also help adolescents receive support in another way. Adolescents seek and receive support from friends when they are in trouble ( D’Avanzo et al, 2012 ; Heerde and Hemphill, 2018 ; Schacter and Margolin, 2019 ; van den Toren et al, 2020 ), such as academic and emotional problems ( Tishby et al, 2001 ; Amemiya and Wang, 2017 ; Zander et al, 2019 ). This tendency can be explained in several ways.…”
Section: Role Of Friendships In the Development Of Peer Support Netwomentioning
confidence: 99%
See 1 more Smart Citation
“…A project was set up to evaluate the extension of preventive Youth Health Care for adolescents, e.g. by conducting a questionnaire and by organizing focus group interviews among adolescents [ 22 ]. For the questionnaire, a power calculation was performed to calculate the target sample size to obtain a statistically significant small to medium effect size of the extension of preventive Youth Health Care for adolescents when compared to a control condition.…”
Section: Methodsmentioning
confidence: 99%
“…However, aspects such as staff turnover, funding, time and material resources challenge schools' capacity to sustain health interventions (Herlitz et al, 2020). In addition, adolescents may perceive barriers to seeking help for behavioural problems from professionals in school and may prefer seeking help from friends and from digital sources (Van Den Toren et al, 2020).…”
Section: Introductionmentioning
confidence: 99%